Structural change, fundamentals, and growth: A framework and case studies - McMillan, Margaret S.; Rodrik, Dani; Sepúlveda, Claudia (International Food Policy Research Institute, 2017)
The volume consists of an overview and seven country studies, written by leading scholars from both developed and developing countries. The overview lays out a unifying framework for thinking about economic growth as a combination of two challenges. The “structural change challenge” is focused on moving resources from traditional low-productivity activities into modern, more productive industries. The “fundamentals challenge” faced by policy makers in the developing world is about how best to develop broad capabilities such as human capital and infrastructure. While the two are inextricably linked, they are conceptually different, and making this distinction is one of the contributions of this book. The overview also includes a description of the common methodology used in the country studies, a discussion of data and measurement issues, and a synthesis of the findings.